Determinants of tetanus toxoid immunization uptake among brides-to-be: a mixed-method analysis - Murniati, Murniati; Pramana, Cipta; Pabidang, Siswanto (Journal of Midwifery, 2024)
This study investigates the factors affecting Tetanus Toxoid (TT) immunization among brides-to-be in Aceh, using a mixed-method approach. Tetanus, a potentially fatal bacterial infection, poses a significant risk, particularly to maternal and neonatal health. Despite government mandates for TT immunization, uptake remains inconsistent. Quantitative data from structured questionnaires assessed respondents' knowledge, attitudes, and healthcare provider support. The qualitative component used in-depth interviews with brides-to-be, healthcare providers, and community leaders to explore contextual factors impacting TT immunization. Results showed that 92.9% of respondents were aged 20-35, indicating the importance of targeting this demographic. While 57.1% held college degrees or higher, a high unemployment rate (35.7%) suggested potential barriers to healthcare access. Misinformation, societal resistance, and religious concerns emerged as key challenges, with misconceptions about vaccine safety contributing to vaccine hesitancy. Recommendations for improving TT immunization uptake include targeted education campaigns, addressing religious and cultural concerns, and simplifying the immunization process. By implementing these strategies, public health authorities can increase TT immunization rates, leading to better maternal and neonatal health outcomes in Aceh